Dear church : a love letter from a black preacher to the whitest denomination in the U.S - Duncan, Lenny (Fortress Press, 2019)
"Lenny Duncan is an unlikely pastor. Formerly incarcerated, formerly homeless, and formerly unchurched, he is now a black preacher in the whitest denomination in the United States: the Evangelical Lutheran Church in America [ELCA]. Shifting demographics and shrinking congregations make the headlines, but Duncan connects the church's lack of diversity to its lack of vitality. sees something else at work--drawing a direct line between the church's lack of diversity and the church's lack of vitality. Part manifesto, part confession, and all love letter, Dear Church offers a bold new vision for the future of the church."--Cover